Understanding the Concept and the Character of Caring for the Environment of Junior High School Students in Indonesia - Ramli, Supian; Novanda, Ramazani; Sobri, Muhammad (Jurnal Pendidikan Progresif, 2022)
Identification of Understanding the Concept and Character of Caring for the Environment. Objectives: The purpose of this study was to determine the relationship between students' responses to the cultural values of the inner tribe, the character of students' environmental care, and student learning outcomes on environmental materials. Methods: This type of research is a mix method research with an explanatory design. Mix method research consists of quantitative research and qualitative research or commonly called mixed research. The sampling technique used in this study was purposive sampling with the research sample being class VIII students at SMPN 01 Muaro Jambi and SMPN 7 Muaro Jambi. Findings: Based on the results of the correlation test with the results of the value of sig. (2-tailed) which is less than 0.05 Conclusion: Based on the correlation test that has been carried out, it can be concluded that there is a relationship between students' responses to the cultural values of the inner tribe, the character of caring for the environment and student learning outcomes in both schools. Keywords: environmental care character, inner tribe, conservation, natural science.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202206